Digital neuromarketing and its importance to develop valuable content in social networks - Cuzquillo Cusquillo, Edgar Alfredo; Tierra, Elizabeth; Rivera Abarca, Ana Lucía; Vergara Zurita, Heidy Elizabeth (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020, 2021)
esearch and deeper studies. Currently there is a discipline known as digital neuromarketing that is based on the application of neuroscientific discoveries to digital marketing strategies, for this reason this research aims to determine the importance of digital neuromarketing in the development of valuable content in companies. social networks. It is clear that we are going through an era of information and knowledge, where communication in social media went from being a trend to becoming a necessity for organizations large and small. Therefore, this research made use of a qualitative and quantitative research approach and an exploratory and descriptive research level. In this case, it was determined that the neuromarketing strategies implemented in the digital field are extremely important to generate valuable content on social networks, with visual content such as images, infographics and videos being the most attractive for users of the city of Riobamba, thus causing a greater interaction (engagement) with the content that is generated, thus generating a symbolic emotional relationship between the brand and the community of a certain product or service.